IDENTIFIKASI INFRASTRUKTUR PENGOLAHAN AIR BERSIH PADA KOMPLEK IPDN KECAMATAN SEGEDONG KABUPATEN MEMPAWAH - Ivan Ami Oktavian; Arif Parabi; Sondang Sylvia Manurung (Fakultas Teknik Universitas Panca Bhakti, 2022)
Based on data from PDAM Segedong District that the area utilizes one spring, the Peniti Besar River Spring with a source capacity of 1000 l/s. The Institute of Domestic Administration or commonly known as IPDN has a campus in the Segedong District where the location is far from the reach of clean water sources, so the closest distance to the IPDN Complex is PDAM Segedong District, Mempawah Regency. The purpose of this research is to know the types of Clean Water Infrastructure for the IPDN Campus area, to know the condition of the PDAM Segedong Subdistrict Infrastructure to support the IPDN Complex, and to know the amount of clean water needs in the IPDN area. The method used in this research is the Observation Method (Observation), Interview Method (Direct Interview) and Instrument Method. The result is the number of students and employees in 2020 with a total of 800 students, 99 civil servants and 177 staff, so the total value of the total need for clean water in the IPDN area is 109800 Liters/Day. In addition, from the calculation results, the results of the plan for Clean Water Needs that must be fulfilled and supplied to the IPDN Complex, Segedong District, Mempawah Regency are 109.800 Liters/Day, with a reservoir capacity of 109.8 m (V), with a transfer pipe dimension of 90 mm and with a pump power of 387,722 Watt.